Odpowiedzi

2010-03-22T17:35:12+01:00
A)-⅗x=-5
x=25/3

g)¾x=-⁴/₉
x=-16/27

h)0,1x=-7
x=-70

2.
d)-(2x-1)=4
-2x+1=4
-2x=3 / : (-2)
x=3/-2

e)2(x+1)=x
2x+2=x
2x-x=-2
x=-2

f)2t-(3t+1)=6
2t-3t-1=6
-t=5 / : (-1)
t= -5
1 5 1
Najlepsza Odpowiedź!
2010-03-22T18:01:49+01:00
F)-3/5x=-5 |*5
-3x=-25 |:(-3)
x=8 i 1/3
spr.-3/5 *25/3=-5
-5=-5
L=P

g)3/4x=-4/9 |*4
3x=-16/9 |:3
x=-16/27
spr.3/4 * (-16/27)=4/9
4/9=4/9
h)0,1x=-7 |:0,1
x=-70
spr.o,1x*-70=-7
-7=-7

d)-(2x-1)-4
-2x+1=4|-1
-2x=3|:-2
x=-1,5
spr.-(2*-1,5-1)=4
-(-3-1)=4
-(-4)=4
4=4
e)2(x+1)=x
2x+2=x|-x, -2
X=-2
spr.
2(-2+1)=-2
2*-1=-2
-2=-2
f)2t-(3t+1)=6
2t-3t-1=6
-t-1=6|+1
-t=7|*-1
t=-7
spr.2*(-7)-(3*(-7)+1)=6
-14-(-21+1)=6
-14-(-20)=6
-14 +20=6
6=6
1 5 1